The challenges of educational leadership : values in a globalized age - Bottery, Mike (Leading teachers, leading schools., 2004)
The author presents critical issues about the purposes of educational leadership. He examines how 'official' concepts of leadership are driven by demands which are not always to the educational, political, or social benefit of practitioners.